Search 73,320 tutors
FIND TUTORS
Ask a question
1 0

How do we rewrite -2y+5= -6x so that y is a function of x. Use Function Notation

Tutors, please sign in to answer this question.

2 Answers

Rewrite -2y+5= -6x so that y is a function of x. Use Function Notation.
 
-2y + 5 = -6x
 
Subtract 5 from both sides:
 
-2y = -5 -6x
 
Divide both sides by -2:
 
f(x) = y = 5/2 + 3x
Hi Tracy;
ANSWER TO YOUR SECOND QUESTION...
-2y+5= -6x
We need to isolate y such that x will be multiplied by its coefficient and added to the constant.  This is to produce the result of y.
Let's subtract 5 from both sides...
-5-2y+5= -6x-5
-2y=-6x-5
Let's divide both sides by -2...
(-2y)/-2=(-6x-5)/-2
y=3x+(5/2)
We will replace y with f(x)...
f(x)=3x+(5/2)
f(x) means function of x.
 
ANSWER TO YOUR FIRST QUESTION...
The y value of both points is the same...
y=-2
This is a straight horizontal line.
The slope is zero, NOT undefined.  It is NOT undefined because slope, by definition, is the change-of-y divided by the change-of-x, also known as rise-over-run.  The change-of-y is zero.  Henceforth, the numerator is zero.  The slope can only be characterized as undefined if the denominator, change-of-x, is zero.
The equation is...
y=-2

Comments

Ty but i just found it out. But could u help me with this one? We never learned it because of snow days.